Parasitoid complex of doryctine wasps (Hymenoptera: Braconidae) reared from Pongamia pinnata (L.) (Fabaciae) coleopteran complex (Coleoptera) with description of two new species from India - Gupta, Ankita; Belokobylskij, Sergey A.; Achterberg, Cornelis Van; Pattar, Rohit; Broad, Gavin R.; Gracy, R. G.; Sushil, S. N. (Zootaxa, 2024)
Two doryctine species, viz., Leluthia pongamiacola Gupta & Belokobylskij, sp. nov. and Sycosoter ordinarius Gupta & Belokobylskij, sp. nov., are described from southern India, reared from coleopteran-infested logs of Pongamia pinnata (L.) Pierre (Fabaceae). Additionally, Ipodoryctes signipennis (Walker, 1860), reared from the same infested logs, is redescribed. A key to the Indian species of the genus Leluthia is suggested. Biological notes of the coleopteran complex are provided.